2021
DOI: 10.3390/mi12111294
|View full text |Cite
|
Sign up to set email alerts
|

A New Design of Porosity Gradient Ti-6Al-4V Encapsulated Hydroxyapatite Dual Materials Composite Scaffold for Bone Defects

Abstract: The tibia of New Zealand White rabbits was used as a model of critical bone defects to investigate a new design of composite scaffold for bone defects composed of dual materials. The all-in-one design of a titanium alloy (Ti-6Al-4V) scaffold comprised the structure of a bone plate and gradient porosity cage. Hydroxyapatite (HAp), a biodegradable material, was encapsulated in the center of the scaffold. The gradient pore structure was designed with 70%-65%-60%-55%-50% porosity, since the stresses could be distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…This finding aligns with previous research, which also demonstrated that Ti6Al4V porous scaffolds exhibit excellent bone integration effects, especially with pore sizes in the range of 600–900 μm and a porosity of 70% ( Taniguchi et al, 2016 ). The appropriate pore size facilitates the ingrowth of new bone tissue and nutrient supply, while a 70% porosity rate closely resembles the porosity rate of physiological bone trabeculae, making it a biomimetic physiological condition that achieves optimal bone integration effects ( Pan et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…This finding aligns with previous research, which also demonstrated that Ti6Al4V porous scaffolds exhibit excellent bone integration effects, especially with pore sizes in the range of 600–900 μm and a porosity of 70% ( Taniguchi et al, 2016 ). The appropriate pore size facilitates the ingrowth of new bone tissue and nutrient supply, while a 70% porosity rate closely resembles the porosity rate of physiological bone trabeculae, making it a biomimetic physiological condition that achieves optimal bone integration effects ( Pan et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…This study can be said to provide theoretical support and reference for femoral bone repair in terms of structure. On the other hand, Pan et al [51] using the New Zealand white rabbit tibia as a critical bone defect model, studied the design of a novel composite scaffold composed of two materials. The integrated design of the titanium alloy (Ti-6Al-4V) scaffold includes the structure of the bone plate and the gradient pore cage.…”
Section: A Bone Scaffold To Repair a Large Femurmentioning
confidence: 99%
“…This mitigates the risk of post-operative migration and significantly reduces the likelihood of complications. Our team has conducted previous studies on bone defects [32,33].…”
Section: Introductionmentioning
confidence: 99%